Cost‐effectiveness of neurostimulation in Parkinson's disease with early motor complications. Issue 8 (10th August 2016) - Dams, Judith; Balzer‐Geldsetzer, Monika; Siebert, Uwe; Deuschl, Günther; Schuepbach, W.M. Michael; Krack, Paul; Timmermann, Lars; Schnitzler, Alfons; Reese, Jens‐Peter; Dodel, Richard; ,
ABSTRACT: Background: Recent research efforts have focused on the effects of deep brain stimulation of the subthalamic nucleus (STN DBS) for selected patients with mild‐to‐moderate PD experiencing motor complications. Objectives: We assessed the cost utility of subthalamic DBS compared with the best medical treatment for German patients below the age of 61 with early motor complications of PD. Methods: We applied a previously published Markov model that integrated health utilities based on EuroQoL and direct costs over patients' lifetime adjusted to the German health care payer perspective (year of costing: 2013). Effectiveness was evaluated using the Parkinson's Disease Questionnaire 39 summary index. We performed sensitivity analyses to assess uncertainty. Results: In the base‐case analysis, the incremental cost‐utility ratio for STN DBS compared to best medical treatment was 22, 700 Euros per quality‐adjusted life year gained. The time to, and costs for, battery exchange had a major effect on the incremental cost‐utility ratios, but never exceeded a threshold of 50, 000 Euros per quality‐adjusted life year. Conclusions: Our decision analysis supports the fact that STN DBS at earlier stages of the disease is cost‐effective in patients below the age of 61 when compared with the best medical treatment in the German health care system. This finding was supported by detailed sensitivity analyses reporting robust results. Whereas the EARLYSTIM study has shown STN DBS to be superior to medical therapy with respect to quality of life for patients with early motor complications, this further analysis has shown its cost‐effectiveness. © 2016 International Parkinson and Movement Disorder Society